بنية الأستفهام في سورة الملك: دراسة تحليلية فنية - القرنى، عقيلة محمد (المؤسسة العربية للتربية والعلوم والآداب, 2020)
تسعى هذه الدراسة إلى درس الاستفهام في سورة الملك على أنه بنية رئيسية ونسق عام، ينتظم الخطاب القرآني فيها من أوله إلى آخره؛ دون سواه من سائر الأساليب الإنشائية الأخرى!؛ مع رصد علل الظاهرة، والوقوف على الدلالات البلاغية التي خرج إليها الاستفهام، والإبانة عن مدى تعالقها مع مجموع القرائن والعناصر اللغوية المصاحبة لها، تحقيقاً لمقاصد السورة وما تتوخاه من غايات.
The study aiming at analysis and study of question form in Surah Al-Mulk as a basic structure and general rule where the Qura’nic address is thoroughly organized. To be a distinguished from other comprehensions styles. In addition to observing the Obvious reasoning and concentrating on the Rhetorical denotations in the question form. Study and analysis of manifestation relationship with argumentations and its accompanied language factors for achieve the purposes of Surah Al Mulk.
Keywords: القرآن الكريم -- سورة الملك -- تفسير القرآن -- ألفاظ القرآن -- الاستفهام